ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK PRIBADI DI KPP PRATAMA BATAM SELATAN - Wau, Fiswanti; Purba, Mortigor Afrizal (SCIENTIA JOURNAL, 2021)
The country of Indonesia is a developing country consisting of thousands is islandsand a wide varityof cultures and abundant natural resources,to develop a country that requires no small amount of costs so that revenues or state revenues really need to be increased, one way to increase state income is from the taxation sector. The greater the tax revenue received, the greater the state’s income, to improve people’s welfare, prosperity and to the effect of service, inpection, and tax sanctions on the level of the compliance of individual taxpayers registered at the KPP Pratama Batam Selatan. The analytical method used in this study is quantitative, the data collection technique is by distributing questionnairesto individual taxpayes registered at the KPP Pratama Batam Selatan totalyng 307,006 taxpayers, the taking at sample af 100 respondents as the object of research. Based on the results of the research service of 12,262 and a tax of 4,895, greater than the table of the table (1,665), which means influential on the rate of compulsory tax, while the examination of -3,582 smaller from the table which means no influence on the service of compulsory tax. Based on the results of the f test, it is known that simultaneously and together service, checks and tax witnesess have a significant effect on the level of personal taxpayer compliance at the KPP Pratama Batam Selatan.